Analysis of the reference open system interconnection model clustering of by MLP and RBF network toolkit - Печурин, Н. К.; Кондратова, Л. П.; Печурин, С. Н. (Problems of Informatization and Control, 2010)
Algorithm of the classification with representing the set of functions’ taxons by the cortege, which implements the learning process of multilayer artificial neural networks (ANN) MLP and RBF, are proposed to apply for the reference open systems interconnection model (OSI RM). The quality criteria for the definition of the cortege are formed using the magnitudes that characterize the relative number of common parameters for each pair of OSI RM functions. By the experimental studies of the algo-rithm changing the thresholds values in the MLP and RBF ANN models’ constraints it is revealed a nonexisting in the classical OSI RM distribution of the functions between the hierarchical levels that stipulates the development of improved recommendations with the appearance of a new technologies